Feeding strategies to improve health and sustainability of dairy cattle - Takiya, Caio Seiti (Kansas State University, 2020)
Dairy farming is a multi-billion industry that produces high-quality sources of protein, vitamins, and minerals in the form of dairy products to an ever-growing world population. The dairy industry, however, has been challenged to produce more milk using feeds that are not desirable for other livestock (i.e. swine and poultry) or human nutrition. High milk producing cows have greater risk of developing metabolic/infectious diseases and reproductive problems, often associated with immune system dysfunction. Feeding strategies during the transition period primarily targeting the modulation of the immune system have shown positive effects on controlling inflammation, measures of cellular immune response, and overall performance of cows. An immunomodulatory feed additive was fed to cows during the dry period and early lactation to evaluate immune cell responses and overall performance. Immune cells were collected from peripheral blood and uterus of cows. The feed additive modulated uterine immune cell response after parturition, where this effect was dependent on parity and day of lactation. Milk responses to this feed additive were influenced by environmental temperature and humidity that cows experienced during 2 wk before and 2 wk after parturition. The administration of sodium salicylate via drinking water during the first week after parturition altered the abundance of inflammatory mediators in subcutaneous adipose tissue of cows. Changes included an increase in abundance of complement system proteins and interleukin-10 signaling, and evidence for greater monocyte infiltration. The metabolic effects of sodium salicylate observed in earlier studies might be associated with changes promoted in adipose tissue. Finally, two experiments were carried out to demonstrate that conventional diets for lactating cows are relatively efficient at converting human-edible foods in milk, returning greater amounts of digestible essential amino acids than the human-edible feeds provided to cows. Findings such as these can provide the dairy industry more tools for improving herd health and promoting sustainability of the dairy industry as a whole.
Keywords: Immunity; OmniGen-AF; Non-steroidal anti-inflammatory drugs; By-product feed